Acquired epidermodysplasia verruciformis in renal‐transplant recipients. Issue 12 (20th August 2020) - Gara, Soumaya; Jones, Meriem; Litaiem, Noureddine; Hedri, Hafedh; Rammeh, Soumaya; Zeglaoui, Faten
Abstract: Acquired epidermodysplasia verruciformis in renal‐transplant recipients is associated with a high risk for developing squamous cell carcinoma. An accurate diagnosis and a regular monitoring in this high‐risk population must be stressed. Abstract : Acquired epidermodysplasia verruciformis in renal‐transplant recipients is associated with a high risk for developing squamous cell carcinoma. An accurate diagnosis and a regular monitoring in this high‐risk population must be stressed.